CP-240 The clinical pharmacist resolves medication relative problems in oncologic patients. is it true?. (25th February 2017) - Borja-Prats, C; Conort, O; Maire, A; Jouinot, A; Thomas-Schoemann, A; Alexandre, J; Brandely, M; Batista, R; Bardin, C
Abstract : Background: Cancer is becoming a chronic disease. Oncology patients have a higher risk of suffering medication related problems (MRPs) due to patient characteristics (ageing populations, polypharmacy and comorbidities) and the toxicity of cancer therapies. The presence of a clinical pharmacist in an oncology ward may be an effective intervention to reduce this risk, and may contribute to the optimisation of therapy and quality of services provided to patients. Purpose: The aim of the study was to characterise pharmacist interventions (PIs) and report acceptance rates by physicians in order to reduce MRPs. Material and methods: A satellite unit pharmacy was established in an oncology ward (27 beds) of a large teaching hospital. Clinical pharmacy services including systematic medication reviews and medication reconciliation were provided daily by the clinical pharmacist. All PIs and their acceptance rate, and MRPs were recorded during the 12 month study period (2015) according to a validated classification system (Act IP). Results: Medication reviews were performed in 2080 patients and 7020 therapy forms were analysed. Detection of MRPs led to 505 PIs that were subdivided into safety PIs (60%) and medication optimisation PIs (40%). The most frequent causes of MRPs in the safety group were: excessive dosage (44%), untreated indications (17%), interactions, especially concerning cytotoxic drugs (12%), and suboptimal dosage (11%). Most common PIs in the safety group were dose modification (41%) and drug discontinuation (23%). The drug classes with more interventions were antiemetic drugs, antithrombotic agents and analgesic drugs. The most frequent cause of MRPs in the optimisation group was inadequate choice of drug related to drug formulary (40%). Medication reconciliation was performed on 210 selected high risk patients and led to 30 PIs. The most repeated medication error was omission (57%). The overall physician acceptance rate was 81% for medication reviews and conciliation processes. Conclusion: Detection and resolution of potential MRPs, as well as high rates of PIs acceptance by physicians, confirm the clinical pharmacist's role in improved patient safety in a multidisciplinary healthcare oncology team. An interesting challenge in the future will be to explore the real clinical impact of PIs. References and/or acknowledgements: Thanks to all clinical pharmacists in our hospital. No conflict of interest